2005
DOI: 10.1007/s10529-005-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electrochemical Analysis of Neuropathy Target Esterase Activity by a Tyrosinase Carbon Paste Electrode Modified by 1-Methoxyphenazine Methosulfate

Abstract: A graphite-paste tyrosinase biosensor was improved by adding 1-methoxyphenazine methosulfate as a mediator. Mediator modification enhanced sensitivity to phenol 4-fold and long-term stability 3-fold. Phenol could be detected at 25 nM (S/N = 2) using an Ag/AgCl reference electrode. The biosensor was used to measure the activity of a toxicologically significant enzyme, neuropathy target esterase (NTE), which yields phenol by hydrolysis of the substrate, phenyl valerate. Using the new biosensor, blood and brain N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
(15 reference statements)
0
10
0
1
Order By: Relevance
“…The tyrosinase electrode was prepared as described below. 39 Graphite/paraffin oil (3.5:1, w/w) was mixed thoroughly and packed firmly into a plastic holder (2 mm diameter). Electrical contact was established by a 0.2-mm copper wire inserted from the rear.…”
Section: Preparation Of Tyrosinase Electrode and Assembly Of Biosensormentioning
confidence: 99%
“…The tyrosinase electrode was prepared as described below. 39 Graphite/paraffin oil (3.5:1, w/w) was mixed thoroughly and packed firmly into a plastic holder (2 mm diameter). Electrical contact was established by a 0.2-mm copper wire inserted from the rear.…”
Section: Preparation Of Tyrosinase Electrode and Assembly Of Biosensormentioning
confidence: 99%
“…Обнаружение НТЭ в циркулирующих лимфоцитах и тромбоцитах [19][20][21][22] позволило использовать данный фермент в качестве биомаркера воздействия нейропатичных ФОС на животных и человека [22][23][24][25][26][27]. Разработанный нашей группой электрохимический метод определения активности НТЭ с использованием биосенсоров на основе тирозиназы позволил проводить измерения активность НТЭ в цельной крови [28][29][30][31], что невозможно сделать с использованием стандартного колориметрического анализа. Созданный биосенсор был использован для установления корреляций между ингибированием НТЭ в головном мозге, лимфоцитах и крови кур через 24 ч после введения нейропатичного соединения O,O-дипропил-O-дихлорвинилфосфата (diPr-DClVP) [29].…”
Section: Introductionunclassified
“…The discovery of blood NTE in circulating lymphocytes and platelets (Dudek and Richardson, 1982;Richardson and Dudek, 1983;Bertoncin et al, 1985;Maroni and Bleecker, 1986) enabled it to be used as a biomarker of animal and human exposure to neuropathic OP compounds (Lotti, 1986(Lotti, , 1987Lotti et al, 1983Lotti et al, , 1986Richardson and Dudek, 1983;Schwab and Richardson, 1986). Furthermore, the development of sensitive tyrosinase-based biosensors allowed us to measure NTE in whole blood (Sigolaeva et al, 2001;Sokolovskaya et al, 2005). The biosensor was used to establish correlations of NTE inhibitions in whole blood with that in lymphocytes and the brain 24 h after dosing hens with a neuropathic OP compound, O,O-dipropyl-Odichlorvinylphosphate (PrDChVP) (Makhaeva et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The biosensor was used to establish correlations of NTE inhibitions in whole blood with that in lymphocytes and the brain 24 h after dosing hens with a neuropathic OP compound, O,O-dipropyl-Odichlorvinylphosphate (PrDChVP) (Makhaeva et al, , 2007. These studies indicated that hen whole blood NTE can be assayed and used as a biomarker of exposure to neuropathic OP compounds (Sigolaeva et al, 2001;Makhaeva et al, 2003Makhaeva et al, , 2007Sokolovskaya et al, 2005).…”
Section: Introductionmentioning
confidence: 99%